Improving Service Levels and Impact on the Poor : A Diagnostic of Water Supply, Sanitation, Hygiene, and Poverty in Indonesia - World Bank (World Bank, Washington, DC, 2017)
The objective of this report is to provide an empirical basis for more inclusive and equitable service delivery in the water and sanitation sector in Indonesia. Although the GoI has established a program and strategy for achieving universal access to water supply and sanitation and zero slums (the 100-0-100 program, which aims for 100 percent access to water supply, zero urban slums, and 100 percent access to sanitation), these targets will be achieved through different service level sub-targets. For water supply, the target is for 40 percent of the population to have access to piped water and 60 percent to non-piped (in urban areas, 60 percent piped and 40 percent non-piped), whereas for sanitation, universal access is defined as 15 percent of the population having access to basic sanitation (a toilet that ensures hygienic separation of human excreta from human contact), 12.5 percent to centralized and decentralized sewerage systems, and 72.5 percent to on-site sanitation with improved fecal waste management. A poor-inclusive approach to universal access—one that improves the ability of and opportunity for the poor and vulnerable to benefit from water and sanitation services—can help to ensure that Indonesia not only achieves its service delivery targets, but that water supply and sanitation become key drivers of a reduction in inequality, enhanced health and well-being, and economic growth and prosperity. Policy recommendations are prioritized based on their expected impact on these development goals, and the strength of the evidence base for the solution proposed.